A Novel Analysis of Improving Displacement Factor Using IVDFC in Distribution Systems - M. Padmarasan; C.T. Manikandan; N. Karthikeyan; L. Jayaprakash; C.S. Ajin Sekhar (Institute of Advanced Engineering and Science, 2017)
In this paper discuss the new approach for improving displacement factor using an Interline Dynamic Voltage Restoring and Displacement Factor Controlling Device (IVDFC) in a distribution system. An Interline Dynamic Voltage Restorer (IDVR) is perpetually engaged in distribution systems to mitigate voltage sag/swell problems. An IDVR simply consists of numerous dynamic voltage restorers (DVRs) sharing a common dc link connecting independent feeders to safe electric power to critical loads. The IDVR is operated that it hold the voltage across the critical load bus terminals constant at system nominal frequency irrespective of the changes occurring in source voltages frequency. While one of the DVRs compensates for the local voltage sag in its feeder, the other DVRs reload the common dc-link voltage. For normal voltage levels, the DVRs should be bypassed. Instead of bypassing the DVRs in normal conditions, this paper proposes operating the DVRs, if needed, to improve the displacement factor (DF) of one of the involved feeders. DF improvement can be achieved via active and reactive power exchange (PQ sharing) between different feeders. To successfully apply this concept, several constraints are addressed throughout the paper. The simulation model for this system is developed using MATLAB which is shown that the voltage across the critical load is regulated completely.